Life : an exploded diagram - Peet, Mal. (Somerville, Mass. : Candlewick Press, 2013)
In 1960s Norfolk, England, seventeen-year-old Clem Ackroyd lives with his mother and grandmother in a tiny cottage, but his life is transformed when he falls in love with the daughter of a wealthy farmer in this tale that flashes back through the stories of three generations.
Booklist starred
School Library Journal starred
Wilson's Senior High School
Booklist starred, September 2011
Bulletin (Center for Children's books), November 2011
Horn Book Starred, November 2011
Keywords: Families -- England -- Juvenile fiction; Social classes -- Juvenile fiction; Coming of age -- Fiction; Family life -- England -- Fiction; Social classes -- Fiction; War -- Fiction; Bildungsromans; Family life -- England -- Fiction; Social classes -- Fiction; War stories; Great Britain -- History -- Elizabeth II, 1952- -- Juvenile fiction; Norfolk (England) -- History -- 20th century -- Juvenile fiction; Great Britain -- History -- Elizabeth II, 1952- -- Fiction; Norfolk (England) -- History -- 20th century -- Fiction; Great Britain -- History -- 1952- -- Fiction; Norfolk (England) -- History -- Fiction; Bildungsromans; War stories